In vivo and in silico studies to identify mechanisms associated with Nurr1 modulation following early life exposure to permethrin in rats. (6th January 2017) - Fedeli, Donatella; Montani, Maura; Bordoni, Laura; Galeazzi, Roberta; Nasuti, Cinzia; Correia-Sá, Luísa; Domingues, Valentina F.; Jayant, Maini; Brahmachari, Vani; Massaccesi, Luca; Laudadio, Emiliano; Gabbianelli, Rosita
Graphical abstract: Highlights: Permethrin crosses the blood–brain barrier. Early life permethrin treatment modifies DNMTs. Monomeric and aggregated α-synuclein levels increase in adolescent rats. No change in Nurr1 promoter methylation was measured. Abstract: The present work was designed to study the mechanisms associated with Nurr1 modulation following early life permethrin (PERM) treatment during rat's life span. Here we demonstrate that PERM exposure in rats, at a dose close to No Observed Adverse Effect Level (NOAEL) for 15 days during neonatal brain development leads to its accumulation long after exposure. In striatum from adolescent rats we detected an increase in DNA methyltransferases (DNMTs) such as DNMT1, DNMT3a, Tyrosine hydroxylase, monomeric and aggregated α-synuclein protein levels. Adult rats showed enhanced DNMT3b and α-synuclein aggregation compared to the control group, while with aging a significant decrease in all biomarkers studied was observed. No changes in Nurr1 promoter methylation in adolescent, adult and old rats were found. In silico studies showed clear evidence of a strong binding interaction between PERM and its metabolite 3-phenoxybenzoic acid with the nuclear orphan receptor Nurr1. These findings suggest that an additional interference with the dopaminergic neuron pathway could occur in situ during PERM accumulation in brain. Therefore, Nurr1 modulation in early life PERM-treated rats, depends on age-related adaptive responses in animals.